Unveiling the Complex Tapestry: A Historical Analysis of the Vietnam War and its Impact on America - Minh, Khánh (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
This journal article presents a comprehensive historical analysis of the Vietnam War and its profound impact on the United States. The study delves into the intricate layers of the conflict, shedding light on its causes, progression, and aftermath. By examining both the military and socio-political dimensions, the article aims to provide a nuanced understanding of the war's complexity and its lasting implications for American society, politics, and foreign policy. The Vietnam War, intricately woven from geopolitical strategies, ideological clashes, and military tactics, holds enduring significance. Emerging from colonial legacies and Cold War dynamics, its escalation echoed the domino theory and containment policy. Amidst guerrilla warfare and air power strategies, the war's reach extended beyond battlefields, resonating in the anti-war movement, cultural expressions, and societal rifts.